The nurse’s role in preventing and diminishing side effects after chemotherapy - Kamińska, Marzena; Ciszewski, Tomasz; Bronikowska, Agnieszka; Ferańska, Maria; Pawlak-Warszawska, Agnieszka; Starosławska, Elżbieta (Polish Journal of Public Health, 2013)
Chemotherapy is one of the basic methods of cancer treatment. The methods of treatment used in oncology have recognized therapeutic value, but each of them is related to the possibility of side effects.Ensuring the effectiveness and safety of the use of anticancer drugs as well as prevention of symptoms occurring as side effects is a fundamental principle of the treatment team.Careful monitoring of the course of treatment can significantly reduce the incidence of side effects.